Investigation of cochlear hair cells and the perception of ultrasound signals in guinea pigs - Wang, Fu-Sen; Nie, Guohui; Huang, Cheng-Cheng; Li, Qian; Li, Tiegang; Zou, Yuee; Zhang, Shaoyan; Ceng, Xinyu (Cellular and Molecular Biology, 2018)
We established a specific ultrasound frequency-dependent model of cochlear injury using bone conduction ultrasounds in the inner ear of guinea pigs at 50 kHz and 83 kHz, to explore the effects of bone conduction ultrasound in the cochlea. To establish a unilateral cochlear damage model, the unilateral cochlea was destroyed. The control group consisted of 50 kHz and 83 kHz bone conduction ultrasounds in unaltered guinea pigs. In each group, cerebral blood oxygenation level dependent (BOLD) effects were determined by functional magnetic resonance imaging (fMRI). The cochlear outer hair cell motor protein, Prestin, and the microfilament protein, F-Actin, were detected. We found that bone conduction ultrasound irradiation at 50 kHz and 83 kHz on the guinea pig inner ear for six hours leads to hair cell damage. Furthermore, low frequency bone conduction ultrasound induces major damage to outer hair cells, while high frequency ultrasound damages both internal and external hair cells. fMRI analysis of cerebral BLOD effects revealed an affected cerebral cortex region of interest (ROI) of 4 and 2, respectively, for the normal control group at 50 kHz or 83 kHz, and 2 for the 83 kHz bone conduction ultrasound cochlear injury group, while 50 kHz bone conduction ultrasound failed to induce the cortical ROI within injury model. Results reveal that the spatial location of guinea pig cochlear hair cells determines coding function for lower ultrasound frequencies, and high frequency bone conduction ultrasound may affect the cochlear spiral ganglion or cranial nerve nucleus in bone conduction ultrasound periphery perception.